Combined chemical and biological treatment of recalcitrant industrial effluents: a case study on kraft pulp wastewater - Mtui, G. Y. S. (Tanzania Journal of Science, 2021)
The chemical degradation of lignin-rich kraft pulp wastewater was carried out by ozonation process flowed by biological treatment using activated sludge. The effects of pH on the degradation of lignin and the production of organic acids were examined experimentally in the ozonolysis of wastewater. The strong alkaline condition enhanced not only the degradation of lignin but also the production of organic acids. The maximum value of BOD5/COD obtained after 12 hours of ozonation was 0.41, indicating that ozone treatment improved the biodegradability of the kraft pulp wastewater. The dynamic behaviours of microbial growth and substrate consumption were investigated in the biodegradation of organic acids using activated sludge. Maleic acid and oxalic acid in the ozonized wastewater were degraded completely by the activated sludge in shake-flasks and bench-scale aerated bioreactor experiments. The immobilized activated sludge culture using polyurethane foam (PUF) was most effective in degrading organic acids in continuous culture condition at an optimum hydraulic retention time (HRT) of 14 hours. The study confirmed that consecutive treatments by ozone and activated sludge are effective methods to treat industrial effluents containing recalcitrant environmental pollutants such as kraft pulp wastewater.